AN ANALYSIS OF DIRECTIVE SPEECH ACTS USED BY THE MAIN CHARACTER IN “DUNKIRK” MOVIE - Elperinda Silaen; Mutiah Mutiah; Murniwati Ndruru; Afriana Afriana (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2022)
When expecting an interlocutor to do an action, the execution of directive acts cannot be ruled out. The speaker must conduct directive acts since they are employed to persuade an interlocutor to do something. This study focused on the execution of directive acts and sought to identify the various types and forms of directive actions. The goal of this research is to assist readers understand the debate of linguistics, particularly directive acts. In practice, this study is likely to assist speakers in doing directive acts in line with intent. Then, interlocutors are intended to understand speakers' intentions through comprehending directed behaviors. As a result, there will be no confusion or ineffectiveness in relation to directive actions. In addition, the varieties of directive actions hypothesis developed by Searle(1979).Searle was used to examine the different forms of directive acts. Those are 5 ask, 4 order, 3 request,2 beg, 2 command ,2 invite,2 advice. In terms of directive actions, the types of directive acts theory developed by Yule(1996) was applied in this study. Declarative, interrogative, and imperative are the three forms. This study used those theories to examine all of the characters' directive actions in the film